2020
DOI: 10.5194/esd-11-775-2020
|View full text |Cite
|
Sign up to set email alerts
|

Climate–groundwater dynamics inferred from GRACE and the role of hydraulic memory

Abstract: Abstract. Groundwater is the largest store of freshwater on Earth after the cryosphere and provides a substantial proportion of the water used for domestic, irrigation and industrial purposes. Knowledge of this essential resource remains incomplete, in part, because of observational challenges of scale and accessibility. Here we examine a 14-year period (2002–2016) of Gravity Recovery and Climate Experiment (GRACE) observations to investigate climate–groundwater dynamics of 14 tropical and sub-tropical aquifer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 90 publications
(134 reference statements)
1
13
0
Order By: Relevance
“…Exceptions include aquifers in northern Africa (R = 0.15-0.33, lags 3-14 mos), Taoudeni in central Africa (R = 0.24), and Karoo in southern Africa (R = 0.28). Focusing on interannual TWS variability alone relative to cumulative monthly precipitation anomalies results in low correlations in most aquifers, except for the Kalahari and Karoo aquifers (R = 0.48-0.82; table 1), indicating longer term precipitation memory in these aquifers, also noted in previous studies [10,51].…”
Section: Climate and Climate Teleconnectionssupporting
confidence: 68%
“…Exceptions include aquifers in northern Africa (R = 0.15-0.33, lags 3-14 mos), Taoudeni in central Africa (R = 0.24), and Karoo in southern Africa (R = 0.28). Focusing on interannual TWS variability alone relative to cumulative monthly precipitation anomalies results in low correlations in most aquifers, except for the Kalahari and Karoo aquifers (R = 0.48-0.82; table 1), indicating longer term precipitation memory in these aquifers, also noted in previous studies [10,51].…”
Section: Climate and Climate Teleconnectionssupporting
confidence: 68%
“…Additionally, the GWS anomaly in Rajasthan, India, calculated using the Gravity Recovery and Climate Experiment (GRACE) estimates, showed an increasing trend in annual recharge [22]. GRACE is an advanced remote sensing product that provides monthly TWS measurements and has proved to be an effective tool for hydrological studies [23,24]. GRACE is being successively utilized for climate studies, quantification of hydrologic processes, and large-scale GWS changes due to limited spatial and temporal in situ groundwater data.…”
Section: Introductionmentioning
confidence: 99%
“…GRACE is being successively utilized for climate studies, quantification of hydrologic processes, and large-scale GWS changes due to limited spatial and temporal in situ groundwater data. Opie et al [23] studied the correlation between GRACE GWS and precipitation for 37 large aquifer systems of the world. Identifying the dominant hydroclimatic variables affecting GRACE-derived groundwater variability using singular value decomposition (SVD) is a novel and the main motivation of this study.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have successfully applied GRACE to quantify variations in groundwater storage through space and time [22][23][24][25][26]. GRACE observations have been particularly useful for detecting variations in groundwater storage in semi-arid areas and to better understand the climate and human-driven factors that are responsible for this variation [18,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to many artesian basins, changes in groundwater stores in the GAB are challenging to investigate owing to its sheer size and the relative scarcity of bore monitoring sites. Despite this difficulty, a wealth of knowledge has been gained from investigations of sub-basins of the GAB using GRACE and bore data [32,33,35,36]. For example, Robertson [37] investigated the unsustainable groundwater extraction in the Surat sub-basin (southeast) of the GAB and found that management of GAB requires proper design concepts and improvements in social and political views.…”
Section: Introductionmentioning
confidence: 99%